2009
DOI: 10.3889/mjms.1857-5773.2009.0060
|View full text |Cite
|
Sign up to set email alerts
|

Noise Induced Sleep Disturbance in Adult Population: Cross Sectional Study in Skopje Urban Centre

Abstract: Aim. To evaluate sleep disturbance caused by environmental noise in residents of Skopje urban centre and to quantify the probability for sleep disturbance related to night-time noise exposure. Methods.Cross sectional study with noise measurements for determination of noise exposure indicator L night . A randomised sample was selected from adult population and directly interviewed with questionnaire for assessment of sleep disturbance.Results. 510 questionnaires were collected and the response rate was 72%, 8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(4 reference statements)
3
8
0
Order By: Relevance
“…The results are similar to those of the LARES study and the study from Skopje, Macedonia [18,19]. The LARES study was conducted under the auspices of the WHO in 8 European countries and showed that 23 % of the population had sleep disorders and the dominant source of noise was traffic noise (including road, rail and air traffic) as well as noise from neighboring flats [18].…”
Section: Discussionsupporting
confidence: 82%
“…The results are similar to those of the LARES study and the study from Skopje, Macedonia [18,19]. The LARES study was conducted under the auspices of the WHO in 8 European countries and showed that 23 % of the population had sleep disorders and the dominant source of noise was traffic noise (including road, rail and air traffic) as well as noise from neighboring flats [18].…”
Section: Discussionsupporting
confidence: 82%
“…[28] Study conducted in The Former Yugoslav Republic of Macedonia has shown that 26% of whole sample had sleep disturbance, and dominant sources were neighborhood noise and road traffic noise. [17,18] The findings have shown similarity with the findings of LARES study. [22] Summary results from the LARES study, organized by WHO and conducted in eight European countries, has shown that 23% of whole sample had sleep disturbance, and dominant noise source were traffic noise (including road traffic, railway and aircraft noise) and neighborhood noise.…”
Section: Sleep Disturbancesupporting
confidence: 88%
“…In this review, one paper from former Yugoslavia, [13] two papers from Serbia, [14,15] one from Slovakia, [16] one paper, [17] and one PhD thesis [18] from The Former Yugoslav Republic of Macedonia and one paper from Lithuania [19] are included aiming to identify the level of sleep disturbance caused by environmental noise in urban adult population considering confounding factors for development of this effect. Results are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Railway and aircraft noise are not serious problems for causing annoyance and sleep disturbance in the exposed population. [36][37][38] These data were disseminated to all the relevant ministries in order to implement these findings in strategies for health, transport, development of urban areas, and urban plans.…”
Section: Slovakiamentioning
confidence: 99%